The future of Korean economic reforms in the automobile, pharmaceutical and consumer electronics industries - Erny Rusly (2008)
This study seeks to evaluate the real impact of the major economic reforms on the global competitiveness of the three industries; namely, automobile, consumer electronics and pharmaceutical, within the manufacturing sector.